PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR PASSING BAWAH MELALUI PERMAINAN BOLAVOLI MINI (STUDI PADA SISWA KELAS XI IPA I SMAN 2 NGANJUK TAHUN AJARAN 2012-2013) - KANDILA RIANDINI, BETHARI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical Education is one of Education form to use the exercising activity as a facility and an education aim. By the physical educSation, the student can be coached to physical activity belonging to sport skills, one of physical activities is a learning of volley ball low passing match.That's why, it is necessary about the increasing of physical education learning at school, so there is necessary that the implementation about learning method which is able to solve that problem. Based on the problem, the writer classified statement of the problems what the increasing of under pass  result study in match that is done with using cooperative learning method through mini volley ball match in physical education subject at 7th grade "D" SMPN 2 Kandangan – Kediri. This research aims to know how big of the increasing in low - passing learning with using the cooperative learning method by mini volley ball match in physical education subject at 7th grade "D" student SMPN 2 Kandangan – Kediri. This research uses PTK method, where the research is divided into two ways, they are 1) First Study and 2) The development consists of two sub ways. Every sub way consists of four steps that are a planning, an action, an observation and a reflection. The research result shows the increasing in every sub way learning where the recapitulation is proofed with there are a cognitive, an attitude and a phsycomotoric to the student on the first study's about 65,06 with five students finishing it with 14% of 36 students totally. The first sub way happens to the increasing is back to become 72,50 by the students finishing it with 42% of 36 students totally.And on the second sub way has increased back to become 79,00 or happening of the increasing's about 6,50 from the first sub way is by the student finishing it with 27 students or 78% of 36 students who are 7th grade "D" SMPN 2 Kandangan Kediri. The conclusion of this research is the implementation of cooperative learning through Mini Volley Ball match can increase the result of under pass by students of 7th grade "D" at SMPN 2 Kandangan – Kediri. Keywords : learning method, cooperative, the result study and a Low - passing.